The effect of storage conditions on the hygiene and sensory status of wild boar meat - Borilova, G; Hulankova, R; Svobodova, I; Jezek, F; Hutarova, Z; Vecerek, V; Steinhauserova, I (Meat science, 2016)
The aim of this study was to compare hygiene status of wild boar meat (shoulder and leg) stored up to 21days at 0°C, 7°C or 15°C. The microbial counts increased gradually in the expected sequence of increasing storage temperatures, with TVC at the end of storage ranging from approx. 2logCFU/g (0°C) to 5logCFU/g (15°C). The lactic acid bacteria and psychrotrophic microflora didn't exceed 2logCFU/g and 2.5logCFU/g, respectively. Whereas odor of the meat stored at 0°C and 7°C was still acceptable at the end of storage, the odor of the meat stored at 15°C was barely acceptable after only 7d of storage and also the content of ammonia was significantly higher. Game meat obtained from animals hunted in the correct way and stored at low temperatures had good microbiological and hygiene status which could be maintained for more than 15days of storage.
Keywords: Game meat; Humans; Sensory analysis; Sus scrofa; mikrobiální viabilita; Lactobacillaceae; Odorants; Color; nízká teplota; chuť; Microbiological quality; lidé; zvířata; Food Storage; Microbial Viability; Ammonia; červené maso; Cold Temperature; Food Microbiology; odoranty; Wild boar; Red Meat; kontaminace potravin; Taste; Food Contamination; barva; Hydrogen-Ion Concentration; Animals; koncentrace vodíkových iontů; skladování potravin; Meat hygiene; amoniak; potravinářská mikrobiologie